Efektivitas Perbedaan Terapi Deep Breathing dan Senam Bugar Lansia terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Muhammad Amin; Devi Permata Sari; Deoni Vioneery (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the differences in the effectiveness of deep breathing therapy and fitness for the elderly to reduce blood pressure in hypertensive patients in the elderly at the Fish Market Health Center in Bengkulu City. This study uses quantitative research with experimental methods, using pre-experimental designs with pretest-posttest design. The results showed that there was no difference in effectiveness between deep breathing therapy and fitness for the elderly. Systolic blood pressure after deep breathing therapy and fitness for the elderly, p value = 0.136 and diastolic blood pressure p value = 0.716 (<0.05). Conclusion, there is no difference in the effectiveness of deep breathing therapy and fitness for the elderly to reduce blood pressure in hypertensive patients in the elderly at the Fish Market Health Center in Bengkulu City. Keywords: Deep Breathing, Hypertension, Exercise Fitness, Elderly, Blood Pressure